Aspek Kecerdasan Emosional dan Spritual dalam al-Qur’an Surat Luqman Ayat 13-19 - Muslim Razali (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
Emotional and spiritual intelligence helps a person to find the meaning of life and happiness. People are not only sufficient with intellectual intelligence but also need emotional intelligence to feel happy about their success. In addition, spiritual intelligence is also needed to feel pious and serve sincerely. Intellectual intelligence is apparently not enough to guarantee decision making, so today people are starting to talk about other intelligences, namely emotional intelligence and spiritual intelligence. In the Al-Quran there is a figure of Luqman who teaches his children about policy advice and contains values of emotional and spiritual intelligence.